Democracy in the digital age: digital agora or dystopia. (2017) - Parycek, Peter; Rinnerbauer, Bettina; Schossböck, Judith
Information and communication technologies (ICTs) affect democracy and the rule of law. Digitalisation has been perceived as a stimulus towards a more participative society or as support to decision making, but not without criticism. Authors draw on a legal review, case studies and quantitative survey data about citizens' view on transparency and participation in the German-speaking region to summarise selected discourses of democratisation via ICTs and the dominant critique. The paper concludes with an outlook on contemporary questions of digital democracy between the dialectic of protecting citizens' rights and citizen control. It is proposed that prospective e-participation projects will concentrate on processes of innovation and creativity as opposed to participation rates. Future investigations should evaluate the contexts in which a more data-driven, automated form of decision making could be supported and collect indicators for where to draw the line between the protection and control of citizens, including research on specific tools.